Gravity Models of Spatial Interaction Behavior - Sen, Ashish; Smith, Tony E. (Springer Berlin Heidelberg, 1995)
Gravity models describe, and hence help predict, spatial flows of commuters, air-travelers, migrants, commodities and even messages. They are one of the oldest and most widely used of all social science models. This book presents an up-to-date, consistent and unified approach to the theory, methods and application of the gravity model - which spans from the axiomatic foundations of such models all the way to practical hints for their use. "I have found no better general method for use in applied research dealing with spatial interaction... It is against this background that the present book by Sen and Smith is most welcomed." Walter Isard
Keywords: Regional/Spatial Science; R & D/Technology Policy; Geography, general; Automotive Engineering; Regional economics; Spatial economics; Economic policy; Geography; Automotive engineering; Regionale Mobilität; Gravitationsmodell